Kinetosis: All You Need to Know - Rashid, Shah Samiur; Ishmael, Ukaegbu Chinonso; Chibuike, Ukaegbu Benjamin (ISSR, 2014)
One of the major fears that grips about 50% of travelers, either by air, road ,sea or any other means of transportation is a very uncompromising situation know as motion sickness. This condition is branded “uncompromising” because ones it sets in, nothing else matters, all attention must be focused on how to resolve it. In medicine, it is called “kinetosis” because it is associated with movements. This condition has made so many people to think a lot whenever they are going to make any form of travelling, and has ultimately reduced some people to limited distances and short destinations. It is also a source of worry to commuters and passengers because a sufferer must be made to get him/herself if the situation gets bad and everybody has to wait until the situation is calmed. This review is aimed at checking the possible cause of kinetosis, its effects on the sufferer and how to manage it. It also reviewed the prevalence of the sickness among adult and children travelers.